JOYERÍA DOMÉSTICA, SENTIMENTAL Y RELIGIOSA. FONDOS DEL MUSEO DE MURCIA - Gutiérrez García, María de los Angeles (Imafronte, 1999)
This paper examined the cataloging of a series of luxury items related to the femenine word of the 19th century. Altought these are not of great significance, they nonetheles refelct certain fashion of the 18th century and popular flockore traditions. The artistic works studied belong to the collection of the Musseum of Murcia, exhibited upto now in the entrance hall of the casa de la cultura.